(untitled) (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 2014)
The well-known Tits construction provides models of the exceptional simple Lie algebras using, as ingredients, a unital composition algebra and a degree three central simple Jordan algebra.